PARTISIPASI MASYARAKAT DALAM MENJAGA KEBERSIHAN DI KELURAHAN BAHU KECAMATAN MALALAYANG KOTA MANADO - BAWOLE, POULA JECQUELINE; LENGKONG, FLORENCE DAICY; LONDA, VERY (Sam Ratulangi University, 2018)
Abstract: A good development process makes people actively participate. One of the programs set by the ManadoCity Government which gives space to the community to directly actively participate in the implementation ofdevelopment is the cleanliness of the environment. This research was conducted to explain the communityparticipation in maintaining cleanliness in the sub-district of Bahu Kecamatan Malalayang Kota Manado. Byusing qualitative research designs it was found that community participation in maintaining environmentalhygiene in urban village Bahu subdistrict Malalayang of Manado City through the acceptance of environmentalhygiene program has not been all done by society such as in obeying garbage garbage, providing garbage athome, participation in hygiene utilization the environment is carried out by utilizing garbage transporters andclean Friday activities, participation in the maintenance of environmental hygiene indicates that not allcommunities maintain good hygieneKeywords: Community Participation, Cleanliness, Environment.